Study on the implementation of biometric device (Fingerprint) in attendance tracking for UiTM students / Norhazura Mohd Zubir - Mohd Zubir, Norhazura (2005)
The use of biometrics in accordance with tracking attendance in secondary educational environments is a very controversial issue. In this research, biometric devices relating to the use of tracking attendance and addressing issues and concerns that educational institutions face in deciding whether or not this biometrics is implemented in attendance tracking for UiTM students. Biometrics Fingerprint device is a popular technique for determination of attendance no matter whether in the working place or for student attendance. Many companies and a few IPT in Malaysian have using it are as a part of daily transaction. With using this biometric Fingerprint device, we can make attendance tracking easier than traditional attendance tracking. A fingerprint is an imprint made by the pattern of skin on the pad of a human finger. These ridges are commonly believed to provide traction for grasping objects. No two humans, not even identical twins, have ever been found to have identical fingerprints. Fingerprints are widely believed to be unique. Also, fingerprints do not change significantly with age. Because of these characteristics, a person's fingerprint can be used as a method to identify human individuals